Solutions to design and construction offacilities for development of small and marginal fields - Toan, Le Huu; Son, Cao Tung; Dung, Le Viet; Han, Bui Trong; Quan, Le Vu (Petrovietnam Journal, 2015)
The paper presents the technological solutions currently applied in the world to design and construction of facilities for development of small and marginal fields. It also shares the solutions which have been studied and applied by Vietsovpetro Joint Venture for development of the small and marginal fields in the blocks managed by Vietsovpetro.